The effects of Orthosiphon stamineus, Morinda citrifolia and Centella asiatica on yogurt fermentation and functional properties / Shamrulazhar Shamzir Kamal. - Shamrulazhar, Shamzir Kamal (2011)
Yogurt containing probiotics is increasingly recognized as nutritious functional food. The objectives of the present study were to investigate the changes of yogurt fermentation in the presence of herbs to determine the viability of Lactobacillus spp. and S. thermophilus and therapeutic (anti-diabetic) values of herbal-yogurts. Yogurt was fermented in the presence either of Orthosiphon stamineus, Morinda citrifolia or Centella asiatica water extract. The pH and titratable acidity (TA) were monitored during yogurt preparation and during 21 days of storage. There were no significant differences in pH and TA between herbal-yogurts and plain-yogurt. All herbal-yogurts had higher (p<0.05) total phenolic content (TPC) and antioxidant activities compared to plain-yogurt. The addition of herbal water extract stimulated Lactobacillus spp. growth with the highest effect seen in C. asiatica–yogurt (1.63x109cfu/ml), followed by O. stamineus –yogurt (1.62x109cfu/ml), M. citrifolia–yogurt (9.50x108cfu/ml) and plain-yogurt (7.00x108cfu/ml). α-amylase inhibition was enhanced by all yogurts with the highest inhibition caused by M. citrifolia-yogurt (61.1±2.3%) followed by O. stamineus-yogurt (60.2±0.4%), C. asiatica-yogurt (56.6±1.2%) and plain-yogurt (51.0±0.5%). Highest inhibition of α-glucosidase activities was shown by C. asiatica-yogurt (28.47±0.51%) followed by M. citrifolia-yogurt (27.04±8.99%), O. stamineus-yogurt (21.49±0.63%) and plain-yogurt (15.87±0.71%). Plain-yogurt showed the best organoleptic score compared to herbal-yogurts for all parameters studied. The plants used in the present studies may be used as food additives for the enhancement of yogurt nutritional and therapeutical properties.